ByzRev 05.2023.031: John Monfasani (ed.), Liber Defensionum contra Obiectiones in Platonem:: Cardinal Bessarion’s Own Latin Translation of His Greek Defense of Plato against George of Trebizond (Byzantinisches Archiv – Series Philosophica 6). Berlin – Boston: De Gruyter 2023. - Malone-Lee, Michael (The Byzantine Review, 2023)
John Monfasani (ed.), Liber Defensionum contra Obiectiones in Platonem: Cardinal Bessarion’s Own Latin Translation of His Greek Defense of Plato against George of Trebizond (Byzantinisches Archiv – Series Philosophica 6). Berlin – Boston: De Gruyter 2023. 242 pp., 5 colour ill. – ISBN 978-3-11-124635-2.